Rapidly evolving aerosol emissions are a dangerous omission from near-term climate risk assessments - Persad, G; Samset, B H; Wilcox, L J; Allen, Robert J; Bollasina, Massimo A; Booth, Ben B B; Bonfils, Céline; Crocker, Tom; Joshi, Manoj; Lund, Marianne T; Marvel, Kate; Merikanto, Joonas; et al. (Environmental Research: Climate, 2023)
Anthropogenic aerosol emissions are expected to change rapidly over the coming decades, driving strong, spatially complex trends in temperature, hydroclimate, and extreme events both near and far from emission sources. Under-resourced, highly populated regions often bear the brunt of aerosols' climate and air quality effects, amplifying risk through heightened exposure and vulnerability. However, many policy-facing evaluations of near-term climate risk, including those in the latest Intergovernmental Panel on Climate Change assessment report, underrepresent aerosols' complex and regionally diverse climate effects, reducing them to a globally averaged offset to greenhouse gas warming. We argue that this constitutes a major missing element in society's ability to prepare for future climate change. We outline a pathway towards progress and call for greater interaction between the aerosol research, impact modeling, scenario development, and risk assessment communities.